The effect of levothyroxine treatment on left ventricular function in subclinical hypothyroidism - Velkoska Nakova V; Krstevska B; Srbinovska Kostovska E; Vaskova O; Georgievska-Ismail Lj (My University, 2018)
Objective: Treatment of subclinical hypothyroidism (ScH), especially the mild form of ScH, is controversial because thyroid hormones influence cardiac function. We investigate left ventricular systolic and diastolic function in ScH and evaluate the effect of 5-month levothyroxine treatment. Subjects and methods: Fifty-four patients with newly diagnosed mild ScH (4.2 <TSH < 10.0 mU/L) and 30 euthyroid subjects matched by age were analysed. Laboratory analyses and an echocardiography study were done at the first visit and after 5 months in euthyroid stage in patients with ScH. Results: Compared to healthy controls, patients with ScH had a lower E/A ratio (1.03 ± 0.29 vs. 1.26 ± 0.36, p < 0.01), higher E/e’ sep. ratio (7.62 ± 2.29 vs. 6.04 ± 1.64, p < 0.01), higher myocardial performance index (MPI) (0.47 ± 0.08 vs. 0.43 ± 0.07, p < 0.05), lower global longitudinal strain (GLS) (-19.5 ± 2.3 vs. -20.9 ± 1.7%, p < 0.05), and lower S wave derived by tissue Doppler imaging (0.077 ± 0.013 vs. 0.092 ± 0.011 m/s, p < 0.01). Levothyroxine treatment in patients with ScH contributed to higher EF (62.9 ± 3.9 vs. 61.6 ± 4.4%, p < 0.05), lower E/e’ sep. ratio (6.60 ± 2.06 vs. 7.62 ± 2.29, p < 0.01), lower MPI (0.43 ± 0.07 vs. 0.47 ± 0.08%, p < 0.01), and improved GLS (-20.07 ± 2.7 vs. -19.55 ± 2.3%, p < 0.05) compared to values in ScH patients at baseline. Furthermore, in all study populations (ScH patients before and after levothyroxine therapy and controls), TSH levels significantly negatively correlated with EF (r = -0.15, p < 0.05), E/A (r = -0.14, p < 0.05), GLS (r = -0.26, p < 0.001), and S/TDI (r = -0.22, p < 0.01) and positively correlated with E/e’ sep. (r = 0.14, p < 0.05). Conclusion: Patients with subclinical hypothyroidism versus healthy individuals had subtle changes in certain parameters that indicate involvement of systolic and diastolic function of the left ventricle. Although the values of the parameters were in normal range, they were significantly different compared to ScH and the control group at baseline, as well as to the ScH groups before and after treatment.The results of our study suggest that patients with ScH must be followed up during treatment to assess improvement of the disease. Some of the echocardiography obtained parameters were reversible after levothyroxine therapy.
Keywords: Subclinical hypothyroidism; thyroid replacement therapy; systolic function; diastolic function